2011
DOI: 10.1021/es103793y
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Oxidation of Arsenite to Arsenate on Ferrihydrite

Abstract: The photochemistry of an aqueous suspension of the iron oxyhydroxide, ferrihydrite, in the presence of arsenite has been investigated using attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR), X-ray absorption near edge structure (XANES), and solution phase analysis. Both ATR-FTIR and XANES show that the exposure of ferrihydrite to arsenite in the dark leads to no change in the As oxidation state, but the exposure of this arsenite-bearing surface, which is in contact with pH 5 water,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 35 publications
(67 reference statements)
5
64
1
4
Order By: Relevance
“…The concentration of As(III) and goethite were chosen to ensure that the ratio of As to Fe (Fe/As z 100)after incubation was appropriate for the determination of the ratio of As(III) and As(V) by XANES analysis. In other studies on As(III) oxidation in the presence of iron oxides, the Fe/As ratio ranged from 5 to 580 (Ona-Nguema et al, 2005Bhandari et al, 2011Bhandari et al, , 2012. The flasks were shaken at 25 C at 150 rpm for 10 h. The adsorption reached equilibrium in 10 h. Abiotic control experiments of goethite only were also conducted.…”
Section: Effect Of Contact Order Of Bacteria and Goethite On The Oxidmentioning
confidence: 99%
“…The concentration of As(III) and goethite were chosen to ensure that the ratio of As to Fe (Fe/As z 100)after incubation was appropriate for the determination of the ratio of As(III) and As(V) by XANES analysis. In other studies on As(III) oxidation in the presence of iron oxides, the Fe/As ratio ranged from 5 to 580 (Ona-Nguema et al, 2005Bhandari et al, 2011Bhandari et al, , 2012. The flasks were shaken at 25 C at 150 rpm for 10 h. The adsorption reached equilibrium in 10 h. Abiotic control experiments of goethite only were also conducted.…”
Section: Effect Of Contact Order Of Bacteria and Goethite On The Oxidmentioning
confidence: 99%
“…Therefore, microbial and photochemical processes are important in the environment because they can cause the reduction and/or oxidation of arsenic and iron Langner et al, 2000;Emett et al, 2001;Bhandari et al, 2011Bhandari et al, , 2012. Once iron oxide minerals are present, arsenic will adsorb onto these minerals and might undergo surface mediated reduction or oxidation reactions (Yan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Abiotic oxidation of As(III) by dissolved oxygen is a possible mechanism of species transformation although the process is relatively slow (Zhao et al, 2011). Recent studies have shown that photoinduced oxidation of As(III) to As(V) can occur in the presence of nanoferrihydrite and goethite (Bhandari et al, 2011(Bhandari et al, , 2012. Bhandari et al (2011) assumed that in As(III)-ferrihydrite system, the oxidation of As(III) occurred on the ferrihydrite surface until the surface becomes saturated with As(V).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations